Evaluation of the Anti-Inflammatory and Anti-Oxidative Effects of Therapeutic Human Lactoferrin Fragments - Pan, Yu; Liu, Zhao; Wang, Yijie; Zhang, Linshen; Chua, Niying; Dai, Lei; Chen, Jun; Ho, Chun Loong (Frontiers in Bioengineering and Biotechnology, 2021)
Chronic inflammation is considered a pressing health issue that needs resolving. Inflammatory disease such as inflammatory bowel disease requires a long-term medical regimen to prevent disease progression. Conventionally, lactoferrin is used to treat mild gastrointestinal tract and skin inflammation. Protease-digested lactoferrin fragments often exhibit improved therapeutic properties compared to full-length lactoferrin (flHLF). However, there are no studies on the use of protease-digested lactoferrin fragments to treat inflammation. Herein, we assess the anti-inflammatory properties of engineered recombinant lactoferrin fragments (rtHLF4, rteHLF1 and rpHLF2) on non-malignant colonic fibroblasts cells and colorectal cancer cells. We found that rtHLF4 is ten times more effective to prevent inflammation compared to flHLF. These results were investigated by looking into the reactive oxygen species (ROS) production, angiogenesis activity and cellular proliferation of the treated cells. We have demonstrated in this study the anti-inflammatory properties of the flHLF and the various lactoferrin fragments. These results complement the anti-cancer properties of these proteins that were demonstrated in an earlier study.